Can we rely on the best trial? A comparison of individual trials and systematic reviews. - Glasziou, P; Shepperd, S; Brassey, J (BioMed Central, 2010)
BACKGROUND: The ideal evidence to answer a question about the effectiveness of treatment is a systematic review. However, for many clinical questions a systematic review will not be available, or may not be up to date. One option could be to use the evidence from an individual trial to answer the question? METHODS: We assessed how often (a) the estimated effect and (b) the p-value in the most precise single trial in a meta-analysis agreed with the whole meta-analysis. For a random sample of 200 completed Cochrane Reviews (January, 2005) we identified a primary outcome and extracted: the number of trials, the statistical weight of the most precise trial, the estimate and confidence interval for both the highest weighted trial and the meta-analysis overall. We calculated the p-value for the most precise trial and meta-analysis. RESULTS: Of 200 reviews, only 132 provided a meta-analysis of 2 or more trials, with a further 35 effect estimates based on single trials. The average number of trials was 7.3, with the most precise trial contributing, on average, 51% of the statistical weight to the summary estimate from the whole meta-analysis. The estimates of effect from the most precise trial and the overall meta-analyses were highly correlated (rank correlation of 0.90).There was an 81% agreement in statistical conclusions. Results from the most precise trial were statistically significant in 60 of the 167 evaluable reviews, with 55 of the corresponding systematic reviews also being statistically significant. The five discrepant results were not strikingly different with respect to their estimates of effect, but showed considerable statistical heterogeneity between trials in these meta-analyses. However, among the 101 cases in which the most precise trial was not statistically significant, the corresponding meta-analyses yielded 31 statistically significant results. CONCLUSIONS: Single most precise trials provided similar estimates of effects to those of the meta-analyses to which they contributed, and statistically significant results are generally in agreement. However, "negative" results were less reliable, as may be expected from single underpowered trials. For systematic reviewers we suggest that: (1) key trial(s) in a review deserve greater attention (2) systematic reviewers should check agreement of the most precise trial and the meta analysis. For clinicians using trials we suggest that when a meta-analysis is not available, a focus on the most precise trial is reasonable provided it is adequately powered.